The Increasing Genetic and Phenotypical Diversity of Congenital Myasthenic Syndromes - McMacken, Grace; Abicht, Angela; Evangelista, Teresinha; Spendiff, Sally; Lochmüller, Hanns (Neuropediatrics, 2017)
The congenital myasthenic syndromes (CMS) are a diverse group of diseases, which result in an increasing range of phenotypes, but which are all due to inherited defects at the neuromuscular junction (NMJ). Although some patients remain genetically undiagnosed, our ability to identify the causative genes has shed new light on the role of previous uncharacterized proteins at the NMJ. Securing the genetic diagnosis can be challenging, but it is of critical importance to allow rational therapeutic intervention. In this review, we summarize the key clinical and pathologic features of the CMS subtypes, outline diagnostic clues, and challenges, and describe the recent advances that have highlighted the overlap between CMS and the muscular dystrophies and peripheral neuropathies.
Keywords: congenital myasthenic syndromes; neuromuscular junction; genetic diagnosis; neurophysiology